Determination the right quantities of food aids for adults in Bera Pahang, Malaysia / Masturina Mansor - Mansor, Masturina (2016)
Natural disasters occur all over the world, and this event can be totally overwhelming for people's lives and the environments in which they live. Usually, malnutrition is one of the threat during the disaster because people are not being able to get the food. Food crises during disaster and food-related emergencies may cause food security or rather insecurity. Both are underlying causes of malnutrition and mortality and also a significant factor in the longer term livelihood security. This aim of a study is to assess the nutritional status of adult who affected by flood, to determine the food intakes and the availability of the food during flood as well as to determine the right of quantity food aids for affected adults during flood disaster. The study design used was retrospective cohort study and being conducted in Bera, Pahang. A total of 105 individuals are randomly collected from affected by the flood. For the underweight categories, male and female respondent shows 9.1% (n = 3) and 5.6% (n = 4), respectively. After the flood disaster, the median number of food intake for both gender were same with the number of food intake was 3 times per day and they do not have a problem with food insecurity. The suggested total energy for male is 2000 kcal while for female slightly lower, 1700 kcal. The rating for the government support of food aids, 79% (n = 79) of respondents are rate as adequate. As all the access to the town are down, food aids are required in order to make sure people of are affected in the flood can get adequate nutrition and thus indicate greater food security.